SILENCE ON THE LEVEL OF CHEKHOV'S CHARACTERS (IN PROSE WORKS) (Proceedings of Southern Federal University. Philology, 2013)
Mukhametov D.Keywords: silence, non-verbal communication, prose works by A.P. Chekhov. The article considers silence as a component of conversation between characters in prose works by A.P. Chekhov. The author focuses on multifaceted nature of silence and determines its specific features as a linguistic phenomenon. Silence is characterized by some functioning peculiarities in literary works. It is interesting to study the reasons of silence occurrence in dialogues between literary characters.